PENGARUH PEMBIAYAAN MUDHARABAH, PEMBIAYAAN MURABAHAH DAN TABUNGAN MUDHARABAH TERHADAP RETURN ON ASSETS (ROA) PADA BPR SYARIAH - fitri maulidatul rohmaniah; Eris Munandar (Jurnal Ekonomi Rabbani, 2021)
The purpose of this study was to determine and analyze the effect of Mudharabah Financing, Murabahah Financing and Mudharabah Savings on Return On Assets (ROA) of Indonesian Sharia People's Financing Banks for the 2015-2020 period. The research method used is descriptive quantitative method. The data used is secondary data. In this study, the analysis used is multiple linear regression analysis, coefficient of determination and hypothesis testing. Based on the results of the analysis of this study, it can be seen that partially Mudharabah Financing has a negative and significant effect on Return On Assets, Murabaha financing has a positive and significant effect on Return On Assets and Mudharabah Savings has a positive and significant effect on Return On Assets at Indonesian Islamic People's Financing Bank for the 2015 period. -2020 and simultaneously Mudharabah Financing, Murabahah Financing and Mudharabah Savings have a significant effect on the Return On Assets (ROA) of Indonesian Sharia Rural Banks for the 2015-2020 period. It is expected that the Indonesian Islamic People's Financing Bank will further improve its performance by minimizing financing risk and increasing the amount of third party funds so that its profitability growth is maximized.